2009
DOI: 10.3109/09638280903071867
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality of life in people with aphasia using a Dutch version of the SAQOL-39

Abstract: Gathering information on QoL after suffering from stroke and from aphasia can lead to a better understanding of the problems involved. The clinical use of instruments such as the SAQoL-39 can probably contribute to a more patient oriented rehabilitation, whereby the focus not only lie in improving linguistic skills but also on reducing the impairments and the handicaps that accompany aphasia and thus on increasing QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 29 publications
2
31
0
2
Order By: Relevance
“…Studies exploring the impact of stroke on QoL have identified several relevant factors in stroke survivors, including gender [6,7], age [6,8,9,10,11,12], marital status [8,9], and educational level [11,13,14]. Patients with right-sided lesions are reported to experience poorer QoL than those with left-sided lesions [9,15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies exploring the impact of stroke on QoL have identified several relevant factors in stroke survivors, including gender [6,7], age [6,8,9,10,11,12], marital status [8,9], and educational level [11,13,14]. Patients with right-sided lesions are reported to experience poorer QoL than those with left-sided lesions [9,15].…”
Section: Introductionmentioning
confidence: 99%
“…The SAQOL-39 has been cross-culturally adapted for use in many countries and translated into several languages including, in Europe, Italian [19], Dutch [20], Greek [21], Slovene and Spanish [22]. The Greek version has been culturally adapted and linguistically validated in mainland Greece [21].…”
mentioning
confidence: 99%
“…However, findings are mixed regarding which domains are affected, possibly due to variability in the comparison groups surveyed. Compared to adults without aphasia but who have also experienced stroke or brain injury, adults with aphasia have reported lower HRQoL on emotional and mental functioning scales on the SF-36 and communication, psychosocial, and total scores of the Stroke and Aphasia Quality of Life Scale (SAQoL) (Manders, Dammekens, Leemans, & Michiels, 2010). However, compared to healthy controls, adults with aphasia showed additional impairments on SF-36 scales measuring general health, pain, physical functioning, and physical impact on role functioning , as well as SAQoL physical and energy scales (Manders et al, 2010).…”
Section: Adult Studiesmentioning
confidence: 99%
“…While these findings suggest that physical aspects of HRQoL may be affected in children with SaLD, the evidence is not compelling or supported by the broader speech-language pathology literature. For example, in studies of adults with aphasia, (e.g., Manders et al, 2010), participants only report lower physical functioning when compared to healthy controls rather than nonaphasic adults who are also post-stroke, demonstrating that physical difficulties relate to comorbid conditions rather than language problems. There would be no reason to expect that SaLD per se would result in lower scores for physical functioning and it is likely that any observed effects are due to co-morbid conditions, as children with SaLD often also have motor difficulties .…”
Section: Physical Domainmentioning
confidence: 99%